The prevalence of mental health among Malaysian university students - Arifin, Suhaili; Abdullah, Siti Salina; Omar, Nor Ezdianie; Mohamed, Nurshuhada; Mohamad Yusop, Yusni; Hamdul Hadi, Noor Muthmainnah (Human Resource Management Academic Research Society, 2023)
The mental health among university students should be given close, and more proper, attention due to the fact that they are the national asset in years to come. Life in the university can be pressurizing to the students as they have to grapple with the process of adaptation, family separation, relationship issues, financial issues, health issues and many others. Nonetheless, the university is not the place to solve a student’s personal problems. Instead, they have to deal with the problems themselves using the resources and facilities that have been provided to them. Those students who fail to manage these challenges are highly exposed to mental health problems and further lead to the academic underperformance. Hence, mental health issues are crucial to be addressed to improve their wellbeing and success. Therefore, this study is conducted to identify the mental health level of the Malaysian students in the university. A total of n=810 students was chosen using a simple random sampling technique. This study employs the Mental Health Inventory (MHI) to collect the data. The result indicates that more than half respondents had moderate to high level of psychological distress =68.9%, anxiety =72.7%, and depression =60.6%. Meanwhile for loss of behavioral or emotional control=42.8% were at moderate to high level. In conclusion, even so the level of mental health among university students needs to be emphasized as the moderate level for this overall psychological distress can change to a higher level. Based on the findings, several suggestions have also been discussed.